Developing novel hybrid reefs to provide both wave energy reduction and opportunities for ecological restoration - Benjamin K. Norris; Borja G. Reguero; Camila Gaido-Lasserre; David Gutierrez-Barcelo; Joseph Bartolai; Michael A. Yukish; Landolf Rhode-Barbarigos; Brian K. Haus; Taylor Squires; Gabriel Barajas Ojeda; Maria Maza; Javier L. Lara; et al. (Coastal Engineering, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Performance evaluation of the access anti-HCV assay on the DxI 9000 immunoassay analyzer - Benoit Visseaux; Jérémie Gautier; Françoise Le Boulaire; Catherine Coignard; Claire Vincent; Sandrine Gréaume; Isabelle Voisin; Gaiane Demirdjian; Magali Karagueuzian; Juliane Hey; Dan W. Rhodes (Next Research, 2026)

BMP9 knockout impairs pulmonary vessel muscularisation and confers aberrant tamoxifen sensitivity - Benjamin J. Dunmore; Stephen Moore; Rowena J. Jones; Joshua Hodgson; Kathryn Auckland; Mark Southwood; Nichola Figg; Nobuhiro Kikuchi; Martin Bennett; Allan Lawrie; Christopher J. Rhodes; Mark R. Toshner; et al. (Angiogenesis, 2025)
Deleterious mutations in the GDF2 gene, encoding BMP9, are causative of pulmonary arterial hypertension and hereditary haemorrhagic telangiectasia. Paradoxically, BMP9 germ-line knockout ( Gdf2 −/− ; Bmp9 KO) and double Bmp9 KO / conditional Bmp10 cKO (dKO) mice exhibit an attenuated response to PAH-inducing stimuli. We asked whether this contradiction is due to the pathological, physiological, or genetic consequences of BMP9 knockout. In Bmp9 KO mice we observed reduced pulmonary vascular smooth muscle cell (SMC) coverage and using RNA-seq analysis of Bmp9 KO mouse lungs identified two novel genes, COLQ and ITGA6 , which were differentially regulated in a human PAH RNA-seq dataset. In order to study BMP10 loss, postnatal tamoxifen treatment was required to induce Bmp10 cKO. As previously reported, in dKO mice we observed cardiomegaly and splenomegaly, as well as hyperplasia and hemosiderosis in the pulmonary vasculature. Surprisingly, tamoxifen treated Bmp9 KO control mice phenocopied these pathological changes in dKO mice and downregulated SMC marker gene transcription. Loss of BMP10 is not critical for severe tissue remodelling in the lung, heart, and spleen, rather Bmp9 KO mice appear sensitive to tamoxifen and BMP9 loss is the primary cause of mild vessel remodelling due to a basal reduction of smooth muscle cell coverage. This study suggests that interaction of the BMP pathway with tamoxifen needs to be carefully considered when studying Bmp9 KO mice and urges caution in the context of tamoxifen use when studying cardiovascular and pulmonary disease models.

Designing modular, artificial reefs for both coastal defense and coral restoration - Benjamin K. Norris; Borja G. Reguero; Joseph Bartolai; Michael A. Yukish; Landolf Rhode-Barbarigos; Brian K. Haus; Gabriel Barajas Ojeda; Maria Maza; Javier L. Lara; Michael W. Beck (Coastal Engineering, 2025)

Population dynamics of the Multimammate rat (Mastomys natalensis) and Makundi’s brush fur rat (Lophuromys makundii) and their implications in disease persistence in Mbulu District, Tanzania - Stella T. Kessy; Christopher Sabuni; Apia W. Massawe; Rhodes Makundi; Alfan A. Rija (European Journal of Wildlife Research, 2024)

Afromontane mosaic vegetation acts as a barrier between small mammals from two savannah biomes in northern Ethiopia - Kiros Welegerima; Yonas Meheretu; Josef Bryja; Getachew Mulualem; Welday Hayelom; Ferej Kedir; Apia W. Massawe; Nsajigwa E. Mbije; Rhodes H. Makundi (Biodiversity and Conservation, 2024)

Immunogenetics, sylvatic plague and its vectors: insights from the pathogen reservoir Mastomys natalensis in Tanzania - Lavinia Haikukutu; Japhet R. Lyaku; Charles M. Lyimo; Seth J. Eiseb; Rhodes H. Makundi; Ayodeji Olayemi; Kerstin Wilhelm; Nadine Müller-Klein; Dominik W. Schmid; Ramona Fleischer; Simone Sommer (Immunogenetics, 2023)
Yersinia pestis is a historically important vector-borne pathogen causing plague in humans and other mammals. Contemporary zoonotic infections with Y. pestis still occur in sub-Saharan Africa, including Tanzania and Madagascar, but receive relatively little attention. Thus, the role of wildlife reservoirs in maintaining sylvatic plague and spillover risks to humans is largely unknown. The multimammate rodent Mastomys natalensis is the most abundant and widespread rodent in peri-domestic areas in Tanzania, where it plays a major role as a Y. pestis reservoir in endemic foci. Yet, how M. natalensis ’ immunogenetics contributes to the maintenance of plague has not been investigated to date. Here, we surveyed wild M. natalensis for Y. pestis vectors, i.e., fleas, and tested for the presence of antibodies against Y. pestis using enzyme-linked immunosorbent assays (ELISA) in areas known to be endemic or without previous records of Y. pestis in Tanzania. We characterized the allelic and functional (i.e., supertype) diversity of the major histocompatibility complex (MHC class II) of M. natalensis and investigated links to Y. pestis vectors and infections. We detected antibodies against Y. pestis in rodents inhabiting both endemic areas and areas considered non-endemic. Of the 111 nucleotide MHC alleles, only DRB*016 was associated with an increased infestation with the flea Xenopsylla . Surprisingly, we found no link between MHC alleles or supertypes and antibodies of Y. pestis . Our findings hint, however, at local adaptations towards Y. pestis vectors, an observation that more exhaustive sampling could unwind in the future.

Modern and prospective technologies for weather modification activities: A first demonstration of integrating autonomous uncrewed aircraft systems - T.P. DeFelice; D. Axisa; John J. Bird; C. Alexander Hirst; Eric W. Frew; R.P. Burger; D. Baumgardner; Gerhard Botha; Henno Havenga; Dan Breed; S. Bornstein; C. Choate; et al. (Atmospheric Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Assemblage structure, vertical distributions and stable‐isotope compositions of anguilliform leptocephali in the Gulf of Mexico - Andrea M. Quattrini; Jennifer McClain‐Counts; Stephen J. Artabane; Adela Roa‐Varón; Tara C. McIver; Michael Rhode; Steve W. Ross (Journal of Fish Biology, 2019)
In August 2007, October 2008 and September–October 2010, 241 Tucker trawl and plankton net tows were conducted at the surface to depths of 1377 m at six locations in the northern and eastern Gulf of Mexico (GOM) to document leptocephalus diversity and determine how assemblage structure, larval size, abundance and isotopic signatures differ across the region and with depth. Overall, 2696 leptocephali representing 59 distinct taxa from 10 families were collected. Five families accounted for 96% of the total catch with Congridae and Ophichthidae being the most abundant. The top four most abundant species composed 59% of the total catch and included: Ariosoma balearicum , Paraconger caudilimbatus , Rhynchoconger flavus and Ophichthus gomesii . Four anguilliform species not previously documented in the GOM as adults or leptocephali were collected in this study, including Monopenchelys acuta , Quassiremus ascensionis , Saurenchelys stylura and one leptocephalus only known from its larval stage, Leptocephalus proboscideus . Leptocephalus catches were significantly greater at night than during the day. Catches at night were concentrated in the upper 200 m of the water column and significantly declined with increasing depth. Leptocephali abundances and assemblages were significantly different between sites on the upper continental slope ( c . 500 m depth) and sites on the middle to lower continental slope ( c . 1500–2300 m). Sites on the lower continental slope had a mixture of deep‐sea demersal, bathypelagic and coastal species, whereas upper‐slope sites contained several numerically dominant species ( e.g ., A. balearicum , P. caudilimbatus ) that probably spawn over the continental shelf and upper slope of the GOM. Standard lengths of the four dominant species differed between sites and years, indicating heterochronic reproduction and potential larval source pools within and outside of the GOM. Stable‐isotope analyses (δ 13 C and δ 15 N) conducted on 185 specimens from six families revealed that leptocephali had a wide range of isotopic values at the family and size‐class levels. Species in the families Muraenidae, Congridae and Ophichthidae had similar δ 15 N values compared with the broad range of δ 15 N values seen in the deep‐sea families Nemichthyidae, Nettastomatidae and Synaphobranchidae. Stable‐isotope values were variably related to length, with δ 15 N values being positively size correlated in ophichthids and δ 13 C values being negatively size correlated in A. balearicum and P. caudilimbatus . Results suggest that leptocephali feed in various water depths and masses, and on different components of POM, which could lead to niche partitioning. Ecological aspects of these important members of the plankton community provide insight into larval connectivity in the GOM as well as the early life history of Anguilliformes.

Correction to: Determining the long-term habitat preferences of the Duke of Burgundy butterfly, Hamearis lucina, on a chalk grassland reserve in the UK - M. P. Hayes; G. E. Hitchcock; R. I. Knock; C. B. H. Lucas; P. K. Chaney; M. W. Rhodes; E. C. Turner (Journal of Insect Conservation, 2018)
In the original publication the order of author was published incorrectly. The correct order is given in this Correction.

Determining the long-term habitat preferences of the Duke of Burgundy butterfly, Hamearis lucina, on a chalk grassland reserve in the UK - M. P. Hayes; M. W. Rhodes; E. C. Turner; G. E. Hitchcock; R. I. Knock; C. B. H. Lucas; P. K. Chaney (Journal of Insect Conservation, 2018)

Effect of synthetic hormones on reproduction in Mastomys natalensis - Apia W. Massawe; Rhodes H. Makundi; Zhibin Zhang; Ginethon Mhamphi; Ming Liu; Hong-Jun Li; Steven R. Belmain (Journal of Pest Science, 2018)

Nutritional composition of honey bee food stores vary with floral composition - Philip Donkersley; Glenn Rhodes; Roger W. Pickup; Kevin C. Jones; Eileen F. Power; Geraldine A. Wright; Kenneth Wilson (Oecologia, 2017)

Goldspotted spinefoot Siganus punctatus (Siganidae) age‐based reproductive life history and fisheries vulnerability - K. Rhodes; D. Hernandez‐Ortiz; M. Ioanis; W. Washington; S. Maxim; K. Olpet; S. Malakai (Journal of Fish Biology, 2017)
Between February 2015 and 2016, samples of the Indo‐Pacific goldspotted spinefoot Siganus punctatus were taken from local fish markets, feeding sites and nursery grounds on the main island of Pohnpei, Micronesia, to ascertain sexual pattern, reproductive seasonality, age, growth and mortality. Microscopic examinations of gonads identified two seasonal peaks in reproduction: February to May and September to December, with evidence of some spawning activity in most months. Ripe females were observed 4 days on either side of the new moon. Females first matured at c . 180 mm fork length ( L F ) and 1 year of age, which coincides with their entry into the fishery. Ninety five per cent of individuals were less than 3 years and the oldest fish were 8 years. To examine the species vulnerability to fishing, a tag‐and‐recapture study was conducted over 4 months in 2015 in a locally managed marine area and at an unprotected site. Findings suggest high residency and high vulnerability to fishing at shallow‐water feeding sites and restricted migration overall. The placement of marine protected areas within critical habitat appears to be an effective conservation strategy for this species, particularly when combined with gear and seasonal market restrictions during vulnerable life‐history phases.

ECG imaging of ventricular tachycardia: evaluation against simultaneous non-contact mapping and CMR-derived grey zone - Walther H. W. Schulze; Zhong Chen; Jatin Relan; Danila Potyagaylo; Martin W. Krueger; Rashed Karim; Manav Sohal; Anoop Shetty; YingLiang Ma; Nicholas Ayache; Maxime Sermesant; Herve Delingette; et al. (Medical & Biological Engineering & Computing, 2017)

Identification of virulence genes in Vibrio spp. isolates from the 2009 Bermuda reef fish mortality event - J Bluford; D Gauthier; M Colasanto; M Rhodes; W Vogelbein; A Haines (Journal of Fish Diseases, 2017)

Smoke and mirrors: The overnight abstinence paradigm as an index of disrupted cognitive function - Jessica D. Rhodes; Larry W. Hawk (Psychopharmacology, 2016)

A deep-sea community, including Lophelia pertusa, at unusually shallow depths in the western North Atlantic Ocean off northeastern Florida - Steve W. Ross; Sandra Brooke; Andrea M. Quattrini; Mike Rhode; J. Carter Watterson (Marine Biology, 2015)

The rulB gene of plasmid pWW 0 is a hotspot for the site‐specific insertion of integron‐like elements found in the chromosomes of environmental P seudomonas fluorescens group bacteria - Glenn Rhodes; Hester Bosma; David Studholme; Dawn L. Arnold; Robert W. Jackson; Roger W. Pickup (Environmental Microbiology, 2014)
Summary The rulAB operon of P seudomonas spp. confers fitness traits on the host and has been suggested to be a hotspot for insertion of mobile elements that carry avirulence genes. Here, for the first time, we show that rulB on plasmid pWW 0 is a hotspot for the active site‐specific integration of related integron‐like elements ( ILE s) found in six environmental pseudomonads (strains FH 1– FH 6). Integration into rulB on pWW 0 occurred at position 6488 generating a 3 bp direct repeat. ILE s from FH 1 and FH 5 were 9403 bp in length and contained eight open reading frames ( ORF s), while the ILE from FH 4 was 16 233 bp in length and contained 16 ORF s. In all three ILE s, the first 5.1 kb (containing ORF s 1–4) were structurally conserved and contained three predicted site‐specific recombinases/integrases and a tetR homologue. Downstream of these resided ORF s of the ‘variable side’ with structural and sequence similarity to those encoding survival traits on the fitness enhancing plasmid pGRT 1 ( ILE FH 1 and ILE FH 5 ) and the NR‐II virulence region of genomic island PAGI ‐5 ( ILE FH 4 ). Collectively, these ILEs share features with the previously described type III protein secretion system effector ILEs and are considered important to host survival and transfer of fitness enhancing and (a)virulence genes between bacteria.

Moving beyond the conceptual: specificity in regional climate change adaptation actions for biodiversity in South East Queensland, Australia - Luke P. Shoo; Julian O’Mara; Karin Perhans; Jonathan R. Rhodes; Rebecca K. Runting; Susanne Schmidt; Lochran W. Traill; Lui C. Weber; Kerrie A. Wilson; Catherine E. Lovelock (Regional Environmental Change, 2014)

The genus Pseudo‐nitzschia (Bacillariophyceae) in New Zealand: analysis of the last decade's monitoring data - L Rhodes; W Jiang; B Knight; J Adamson; K Smith; V Langi; M Edgar (New Zealand Journal of Marine and Freshwater Research, 2013)
The diatom genus Pseudo‐nitzschia blooms throughout New Zealand's coastal waters. More than a decade of monitoring data were analysed in this study and seasonality was a significant factor in the appearance of Pseudo‐nitzschia blooms. Austral spring and summer were the main bloom periods, although there were regional differences. Between January 2000 and August 2011, 8.4% of 29,000 seawater samples analysed for Pseudo‐nitzschia exceeded the voluntary trigger level for biotoxin testing (10×10 4 cells l −1 ), and these were analysed by fluorescent in situ hybridisation (FISH) assays. Pseudo‐nitzschia fraudulenta and P. pseudodelicatissima (low domoic acid [DA] producers) were the dominant bloom formers throughout New Zealand (each contributing 25%) followed by the highly toxic P. australis (10%). Shellfish flesh testing for DA was triggered on 8477 occasions between 2000 and 2011, but no samples exceeded the regulatory limit (20 mg/kg); the maximum concentration was 13 mg/kg (Marlborough Sounds, mid‐winter 2010).

Predicting species distributions for conservation decisions - Antoine Guisan; Reid Tingley; John B. Baumgartner; Ilona Naujokaitis‐Lewis; Patricia R. Sutcliffe; Ayesha I. T. Tulloch; Tracey J. Regan; Lluis Brotons; Eve McDonald‐Madden; Chrystal Mantyka‐Pringle; Tara G. Martin; Jonathan R. Rhodes; et al. (Ecology Letters, 2013)
Species distribution models (SDMs) are increasingly proposed to support conservation decision making. However, evidence of SDMs supporting solutions for on‐ground conservation problems is still scarce in the scientific literature. Here, we show that successful examples exist but are still largely hidden in the grey literature, and thus less accessible for analysis and learning. Furthermore, the decision framework within which SDMs are used is rarely made explicit. Using case studies from biological invasions, identification of critical habitats, reserve selection and translocation of endangered species, we propose that SDMs may be tailored to suit a range of decision‐making contexts when used within a structured and transparent decision‐making process. To construct appropriate SDMs to more effectively guide conservation actions, modellers need to better understand the decision process, and decision makers need to provide feedback to modellers regarding the actual use of SDMs to support conservation decisions. This could be facilitated by individuals or institutions playing the role of ‘translators’ between modellers and decision makers. We encourage species distribution modellers to get involved in real decision‐making processes that will benefit from their technical input; this strategy has the potential to better bridge theory and practice, and contribute to improve both scientific knowledge and conservation outcomes.

Towards personalized clinical in-silico modeling of atrial anatomy and electrophysiology - Martin W. Krueger; Walther H. W. Schulze; Kawal S. Rhode; Reza Razavi; Gunnar Seemann; Olaf Dössel (Medical & Biological Engineering & Computing, 2013)

In-silico modeling of atrial repolarization in normal and atrial fibrillation remodeled state - Martin W. Krueger; Andreas Dorn; David U. J. Keller; Fredrik Holmqvist; Jonas Carlson; Pyotr G. Platonov; Kawal S. Rhode; Reza Razavi; Gunnar Seemann; Olaf Dössel (Medical & Biological Engineering & Computing, 2013)

M ycobacterium avium subspecies paratuberculosis is widely distributed in B ritish soils and waters: implications for animal and human health - Glenn Rhodes; Peter Henrys; Bruce C. Thomson; Roger W. Pickup (Environmental Microbiology, 2013)
Summary In the first comprehensive geographical survey of distribution in G reat B ritain, M ycobacterium avium ssp. paratuberculosis ( MAP ) was detected in 115 of 1092 (10.5%) soil cores, in the range of 5 × 10 2 to 3 × 10 6 MAP cell equivalents ( CE ) g −1 wet weight soil with the majority of the positive PCR reactions ( n = 75; 65%) occurring around the limit of detection (500–5000 CE g −1 wet weight soil). The distribution of MAP significantly increased from N orth to S outh and was significantly correlated with increasing cattle numbers over the same longitudinal axis. Similarly MAP occurrence significantly increased towards easterly latitudes although none of the parameters measured were associated. Comparisons of land use indicated that MAP was widely distributed in both farming and non‐farming areas. Soil core samples taken from the rivers W yre and D ouglas catchments ( L ancashire, UK ) and river T ywi ( S outh W ales) were negative for MAP . However, river monitoring showed a consistent presence of MAPs throughout those catchments over a 6‐month period. We concluded that MAP is widely distributed within and outside the confines of the farming environment; its geographical distribution is wider than originally anticipated and; monitoring rivers describes the MAP status of catchment better than individual soil samples.

Fishing groupers towards extinction: a global assessment of threats and extinction risks in a billion dollar fishery - Yvonne Sadovy de Mitcheson; Matthew T Craig; Athila A Bertoncini; Kent E Carpenter; William W L Cheung; John H Choat; Andrew S Cornish; Sean T Fennessy; Beatrice P Ferreira; Philip C Heemstra; Min Liu; Robert F Myers; et al. (Fish and Fisheries, 2013)
Groupers are a valuable fishery resource of reef ecosystems and are among those species most vulnerable to fishing pressure because of life history characteristics including longevity, late sexual maturation and aggregation spawning. Despite their economic importance, few grouper fisheries are regularly monitored or managed at the species level, and many are reported to be undergoing declines. To identify major threats to groupers, the International Union for Conservation of Nature (IUCN) Red List criteria were applied to all 163 species. Red List assessments show that 20 species (12%) risk extinction if current trends continue, and an additional 22 species (13%) are considered to be Near Threatened. The Caribbean Sea, coastal Brazil and Southeast Asia contain a disproportionate number of Threatened species, while numerous poorly documented and Near Threatened species occur in many regions. In all, 30% of all species are considered to be Data Deficient. Given that the major threat is overfishing, accompanied by a general absence and/or poor application of fishery management, the prognosis for restoration and successful conservation of Threatened species is poor. We believe that few refuges remain for recovery and that key biological processes (e.g. spawning aggregations) continue to be compromised by uncontrolled fishing. Mariculture, through hatchery‐rearing, increases production of a few species and contributes to satisfying high market demand, but many such operations depend heavily on wild‐caught juveniles with resultant growth and recruitment overfishing. Better management of fishing and other conservation efforts are urgently needed, and we provide examples of possible actions and constraints.

The first report of Vulcanodinium rugosum (Dinophyceae) from the South China Sea with a focus on the life cycle - N Zeng; H Gu; KF Smith; LL Rhodes; AI Selwood; W Yang (New Zealand Journal of Marine and Freshwater Research, 2012)
An individual non‐motile (NM) cell was isolated from a surface sediment sample collected in Guangxi, China and subsequently established as a dinoflagellate strain in culture. The motile cells are 22.5–32.5 µm long and 20.0–30.0 µm wide, with a plate formula of Po, X, 4′, 3a, 7″, 6c, 5(?)s, 5″′, 2″″, fitting the description of Vulcanodinium rugosum . The Chinese strain shares 99.8%, 97.4% and 96.7% similarity (LSU sequence) with those from Australasia, France and Japan. Asexual division of V. rugosum takes place either in the thecate motile stage or within a NM division cell. Motile cells divided by binary fission inside the parent cell and transformed to NM division cells within 24 h. The NM cell underwent one to three consecutive divisions within the parent wall. The divisions were not always synchronous and neither was the release of motile cells from the NM cells. It generally took 4 to 6 days for the NM cells to complete one division. NM cells survived for 1 month at 4 °C in the dark, suggesting that they might play an important role in species dispersal. A novel pinnatoxin was detected at 20 pg cell −1 and no other known pinnatoxins (A–G) were detected.

The effects of varenicline on attention and inhibitory control among treatment-seeking smokers - Jessica D. Rhodes; Larry W. Hawk; Rebecca L. Ashare; Nicolas J. Schlienz; Martin C. Mahoney (Psychopharmacology, 2012)

Salt Spray Induces Osmotic Adjustment and Tissue Rigidity in Smooth Cordgrass, Spartina alterniflora (Loisel.) - Brant W. Touchette; Kirsten L. Rhodes; Gracen A. Smith; Mariana Poole (Estuaries and Coasts, 2009)

Biomass with capture: negative emissions within social and environmental constraints: an editorial comment - James S. Rhodes; David W. Keith (Climatic Change, 2008)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

The evolving story of Mycobacterium tuberculosis clade members detected in fish - I M Kaattari; M W Rhodes; S L Kaattari; E B Shotts (Journal of Fish Diseases, 2006)
Advances in molecular analyses have permitted documentation of an increasing spectrum of mycobacteria infecting fish. Although some of these mycobacteria are not closely related, several species belong to the Mycobacterium tuberculosis clade. One member of the clade, M. marinum , is well known as an agent of piscine mycobacteriosis. Three other clade species, M. shottsii , M. pseudoshottsii and M. ‘chesapeaki’ , have recently been identified as predominant disease agents in a widespread, continuing epizootic in wild striped bass of the Chesapeake Bay. A fifth clade member, M. ulcerans , has recently been indirectly detected in wild, African cichlid fish. As M. ulcerans is the third most common human mycobacterial infection worldwide, even such indirect evidence of M. ulcerans in fish must be more thoroughly investigated. Complicating the differentiation of these clade members is the growing recognition of intraspecies and interspecies variation in phenotypes, genes and virulence. Thus, researchers must be aware of the variety of piscine isolates within the M. tuberculosis clade. This review summarizes the methods of detection and differentiation for this important group of mycobacteria.

Progesterone’s effects to reduce anxiety behavior of aged mice do not require actions via intracellular progestin receptors - C. A. Frye; K. Sumida; B. C. Dudek; J. P. Harney; J. P. Lydon; B. W. O’Malley; D. W. Pfaff; M. E. Rhodes (Psychopharmacology, 2006)

Applying Network Analysis to the Conservation of Habitat Trees in Urban Environments: a Case Study from Brisbane, Australia - MONIKA RHODES; GRANT W. WARDELL‐JOHNSON; MARTIN P. RHODES; BEN RAYMOND (Conservation Biology, 2006)
In Australia more than 300 vertebrates, including 43 insectivorous bat species, depend on hollows in habitat trees for shelter, with many species using a network of multiple trees as roosts. We used roost‐switching data on white‐striped freetail bats ( Tadarida australis ; Microchiroptera: Molossidae) to construct a network representation of day roosts in suburban Brisbane, Australia. Bats were caught from a communal roost tree with a roosting group of several hundred individuals and released with transmitters. Each roost used by the bats represented a node in the network, and the movements of bats between roosts formed the links between nodes. Despite differences in gender and reproductive stages, the bats exhibited the same behavior throughout three radiotelemetry periods and over 500 bat days of radio tracking: each roosted in separate roosts, switched roosts very infrequently, and associated with other bats only at the communal roost. This network resembled a scale‐free network in which the distribution of the number of links from each roost followed a power law. Despite being spread over a large geographic area (>200 km 2 ), each roost was connected to others by less than three links. One roost (the hub or communal roost) defined the architecture of the network because it had the most links. That the network showed scale‐free properties has profound implications for the management of the habitat trees of this roosting group. Scale‐free networks provide high tolerance against stochastic events such as random roost removals but are susceptible to the selective removal of hub nodes. Network analysis is a useful tool for understanding the structural organization of habitat tree usage and allows the informed judgment of the relative importance of individual trees and hence the derivation of appropriate management decisions. Conservation planners and managers should emphasize the differential importance of habitat trees and think of them as being analogous to vital service centers in human societies.

Spawning aggregations of Lutjanus cyanopterus (Cuvier) on the Belize Barrier Reef over a 6 year period - W. D. Heyman; B. Kjerfve; R. T. Graham; K. L. Rhodes; L. Garbutt (Journal of Fish Biology, 2005)
Cubera snapper Lutjanus cyanopterus aggregated to spawn at Gladden Spit, a salient sub‐surface reef promontory seaward of the emergent reef and near the continental shelf edge of Belize. Their spawning aggregations typically formed 2 days before to 12 days after full moon from March to September 1998–2003 within a 45 000 m 2 reef area. Peak abundance of 4000 to 10 000 individuals was observed between April and July each year, while actual spawning was most frequently observed in May. Spawning was observed consistently from 40 min before to 10 min after sunset within a confined area ≤1000 m 2 . Data suggested that cubera snapper consistently formed seasonal spawning aggregations in relation to location, photoperiod, water temperature and lunar cycle, and that spawning was cued by time of day but not tides. The cubera snapper aggregation site was included within the Gladden Spit Marine Reserve, a conditional no‐take fishing zone.

Bury, Burn or Both: A Two-for-One Deal on Biomass Carbon and Energy - David W. Keith; James S. Rhodes (Climatic Change, 2002)

Quantitative Electroencephalography (QEEG) and Neuropsychological Syndrome Analysis - B. V. Shenal; R. D. Rhodes; T. M. Moore; D. A. Higgins; D. W. Harrison (Neuropsychology Review, 2001)

Timing of Late Quaternary glaciations in the Himalayas of northern Pakistan - Benedict W. Richards; Lewis A. Owen; Edward J. Rhodes (Journal of Quaternary Science, 2000)

Timing of Late Quaternary glaciations in the Himalayas of northern Pakistan - Benedict W. Richards; Lewis A. Owen; Edward J. Rhodes (Journal of Quaternary Science, 2000)

Relative Distribution of Polychlorinated Biphenyls Among Tissues of Neonatal American Alligators ( Alligator mississippiensis ) - T. A. Bargar; C. Sills-McMurry; R. L. Dickerson; W. E. Rhodes; G. P. Cobb (Archives of Environmental Contamination and Toxicology, 1999)

Relic permafrost structures in the Gobi of Mongolia: age and significance - Lewis A. Owen; Ben Richards; Edward J. Rhodes; W. Dickson Cunningham; Brian F. Windley; J. Badamgarav; D. Dorjnamjaa (Journal of Quaternary Science, 1998)

Petrology and geochronology of basalt breccia from the 1996 earthquake swarm of Loihi seamount, Hawaii: magmatic history of its 1996 eruption - Michael O. Garcia; Kenna H. Rubin; Marc D. Norman; J. Michael Rhodes; David W. Graham; David W. Muenow; Khalil Spencer (Bulletin of Volcanology, 1998)

Hymenopterous EGG-pupal and larval-pupal parasitoids ofCeratitis capitata andAnastrepha spp. [Dip.: Tephritidae] in Costa Rica - R. A. Wharton; F. E. Gilstrap; R. H. Rhode; M. Fischel-m; W. G. Hart (BioControl, 1981)

The introduction and establishment of parasites of citrus blackfly,Aleurocanthus woglumi in Florida [Hem.: Aleyrodidae] - W. G. Hart; A. Selhime; D. P. Harlan; S. J. Ingle; R. M. Sanchez; R. H. Rhode; C. A. Garcia; J. Caballero; R. L. Garcia (BioControl, 1978)

Infection of chick embryo tracheal organ cultures with influenza a2 (Hong Kong) virus - P. Blaskovic; A. J. Rhodes; F. W. Doane; N. A. Labzoffsky (Archives of Virology, 1972)

A possible new enterovirus serotype isolated in ontario - F. A. Richter; A. J. Rhodes; L. W. Macpherson; N. A. Labzoffsky (Archives of Virology, 1971)

Substrate binding by crude membranes and solubilized membrane extracts fromPseudomonas natriegens - Martha E. Rhodes; W. J. Payne (Antonie van Leeuwenhoek, 1968)